PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASIONAL DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Nor Zafira Binti Ramzil Huda; Jeni Susyanti; M. hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of organizational culture, organizational commitment and leadership partially or simultaneously on employee performance. The data collection method uses a questionnaire with a sample of 64 respondents taken using proportional random sampling. Data analysis using normality test, classic assumption test, multiple linear regression and hypothesis test (F test and t test). The results showed that that organizational culture simultaneously influenced employee performance; organizational commitment partially influences employee performance; leadership has a partial effect on employee performance. Organizational culture variables, organizational commitment and leadership partial  influence employee performance. Keywords:  organizational culture, organizational commitment and leadership, employee performance